2020
DOI: 10.2139/ssrn.3579206
|View full text |Cite
|
Sign up to set email alerts
|

It Takes a Village: The Economics of Parenting with Neighborhood and Peer Effects

Abstract: As children reach adolescence, peer interactions become increasingly central to their development, whereas the direct influence of parents wanes. Nevertheless, parents may continue to exert leverage by shaping their children's peer groups. We study interactions of parenting style and peer effects in a model where children's skill accumulation depends on both parental inputs and peers, and where parents can affect the peer group by restricting who their children can interact with. We estimate the model and show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In Tables D. 3 and D.4, we perform a similar exercise with the sample we use in our individualfixed effects analysis. We start with a stripped-down specification in column (1), which includes no controls, and we gradually add controls as we move to column (6), which includes block-group fixed effects, time fixed effects, cohort fixed effects, race fixed effects and gender fixed effects. In column (7), we present the estimated effects from our fixed effects model for the same sample.…”
Section: Gradual Addition Of Controlsmentioning
confidence: 99%
“…In Tables D. 3 and D.4, we perform a similar exercise with the sample we use in our individualfixed effects analysis. We start with a stripped-down specification in column (1), which includes no controls, and we gradually add controls as we move to column (6), which includes block-group fixed effects, time fixed effects, cohort fixed effects, race fixed effects and gender fixed effects. In column (7), we present the estimated effects from our fixed effects model for the same sample.…”
Section: Gradual Addition Of Controlsmentioning
confidence: 99%
“…Therefore, direct exposure to treated children who live in the same neighborhood is a likely mechanism that can generate spatial spillover effects. 1 The second channel is parental interactions. While Sociology presents a useful guide, observational studies in the other sciences have also shown the import of this channel.…”
Section: Turning Tomentioning
confidence: 99%
“…Control Treated , we investigate whether children of different races (or gender) benefit differently from spillover effects. We do so by estimating equation (1), separately by race and gender.…”
Section: Pooledmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there is a small empirical literature examining parents' paternalistic behavior towards their children. For instance, there is evidence that imposing limits on children's leisure activities (Cosconati, 2012) and restricting children's choices of friends (Agostinelli et al, 2020) impacts human capital formation. Closely related to our study, Tungodden (2019) investigates parents' paternalistic preferences in the context of their children's competitiveness.…”
Section: Introductionmentioning
confidence: 99%